2018
DOI: 10.1136/bmjopen-2018-022488
|View full text |Cite
|
Sign up to set email alerts
|

Can occupational therapist-led home environmental assessment prevent falls in older people? A modified cohort randomised controlled trial protocol

Abstract: IntroductionFalls and fall-related injuries are a serious cause of morbidity and cost to society. Environmental hazards are implicated as a major contributor to falls among older people. A recent Cochrane review found an environmental assessment, undertaken by an occupational therapist, to be an effective approach to reducing falls. However, none of the trials included a cost-effectiveness evaluation in the UK setting. This protocol describes a large multicentre trial investigating the clinical and cost-effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 30 publications
0
18
0
5
Order By: Relevance
“…This two-arm RCT was embedded within OTIS, which is a UK-based modified cohort RCT. The protocol for the OTIS trial has been published previously 18 . In brief, the OTIS trial aimed to assess whether home environmental assessment and modification, led by an occupational therapist (OT), could reduce risk of falling among community dwelling, older adults at elevated risk of falling.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This two-arm RCT was embedded within OTIS, which is a UK-based modified cohort RCT. The protocol for the OTIS trial has been published previously 18 . In brief, the OTIS trial aimed to assess whether home environmental assessment and modification, led by an occupational therapist (OT), could reduce risk of falling among community dwelling, older adults at elevated risk of falling.…”
Section: Methodsmentioning
confidence: 99%
“…In this paper we describe an embedded RCT (or ‘study within a trial’ [SWAT]) designed to evaluate the effectiveness of including a pen within the trial invitation pack on the recruitment of older adults, identified from GP database searches, into the Occupational Therapist Intervention Study (OTIS) 18 . Specifically, this RCT evaluated the impact of providing pens on subsequent recruitment rates into the OTIS trial, as well as return rates of recruitment documentation, eligibility of respondents, and the retention of participants.…”
Section: Introductionmentioning
confidence: 99%
“…This trial was embedded within the NIHR Health Technology Assessment (HTA) funded Occupational Therapist Intervention Study (OTIS) 10 (Programme grant number 14/49/149). The OTIS study is an RCT that aims to evaluate the clinical and cost effectiveness of an occupational therapist (OT) intervention to reduce falls in high risk older people.…”
Section: Methodsmentioning
confidence: 99%
“…Our aim was to undertake a study within a trial (SWAT) to determine whether the number of participants recruited to a trial can be improved by writing the potential participant’s name by hand, versus printing the name, on the invitation letter. By embedding a study within a RCT currently being coordinated by the York Trials Unit (YTU; University of York), the NIHR-funded OTIS study 10 , the effects of the intervention could be tested within a pragmatic context without the additional costs of participant recruitment.…”
Section: Introductionmentioning
confidence: 99%
“…The OTIS trial aims to evaluate effectiveness of occupational therapist led environmental assessment and modification delivered to older people at moderate to high risk of falls 23. To date, 1331 older people have been randomised to high intensity environmental assessment and modification or usual care control.…”
Section: Is Ongoing Research Likely To Provide Relevant Evidence?mentioning
confidence: 99%